Synergy between genetics and nutrition: a systematic review of factors affecting performance in dairy cows - Qin, Danqing; Gao, Rui; Ji, Dejun (Frontiers in Animal Science, 2025)
With the increasing global demand for dairy products, the improvement of cow performance has become the core topic of the development of dairy farming industry, and the synergy of genetics and nutrition will become one of the keys to solve this problem. Based on the latest research progress and integration of existing studies, we systematically reviewed the effects of genetic and nutritional factors (as well as their synergistic interactions) on dairy cow performance. Genetic factors can improve key performance indicators such as milk yield, milk protein percentage and milk fat percentage by regulating specific genes and their key pathways. At the same time, nutritional intervention for dairy cows, such as optimizing diet structure and adding relevant functional additives, can also significantly improve the key performance indicators of dairy cows. The synergy of the two factors, through the bridge mediated by the rumen microbial community, can improve the genetic potential of production traits with genetic factors as the dominant factor and nutritional factors as the auxiliary factor to maximize the expression of genetic potential, or break through the limitation of a single factor. However, there is a lack of in-depth analysis and research on the underlying molecular mechanisms of this key pathway. The vast majority of the related studies that have been conducted only focus on the changing patterns of apparent traits through comparative experiments. As a result, an accurate linkage model between genetic and nutritional factors could not be established, limiting the development of practical solutions for sustainable and efficient animal husbandry. Future research can focus on more in-depth analysis using multi-omics technology, especially on the deeper molecular mechanism of the nutrition-genetic-rumen microbial-performance pathway, so as to promote a closer linkage between genetic and nutritional factors and provide a feasible method for the continuous and efficient development of animal husbandry.